Peningkatkan Mutu Pembelajaran Melalui Supervisi Aktif di SMPN 1 Sangatta Selatan - Umi Kalsum; Juliana; Cindy; Iswanto; Ratna Dwi Ramdhani (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2024)
Education is a fundamental pillar in creating quality human resources. One of the main keys to achieving superior quality education is the quality of learning that takes place in the classroom. However, South Sangatta 1 Middle School has problems with variations in the quality of teaching between teachers which are still quite significant and student participation in the learning process is still not optimal. This can be seen from the low level of attendance, active involvement in class discussions, and uneven learning outcomes. This research uses a qualitative research approach, with a case study research design. The case study was chosen because this research aims to explore and understand in depth the implementation of active supervision in improving the quality of learning at SMPN 1 Sangatta Selatan. Active supervision has proven to be effective in improving the quality of learning at SMPN 1 Sangatta Selatan. This can be seen from several indicators, namely teachers who take part in the active supervision program show an increase in their ability to develop and implement effective teaching methods and students who take part in the active supervision program show an increase in their participation in the learning process. Active supervision is an effective strategy to improve the quality of learning at SMPN 1 Sangatta Selatan. Active supervision can help teachers to improve the quality of their teaching, thereby increasing student participation and learning outcomes.